KEEFEKTIFAN METODE BILINGUAL INTENSIF UNTUK KEMAMPUAN MEMBACA DAN MENULIS PADA PENDIDIKAN KEAKSARAAN MASYARAKAT SAMIN BLORA - Melati Indri Hapsari; Sanoto Hadi (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
This research aimed to know if in Samin community reading and writing skills of literacy education participants taught with intensive bilingual method are better than those taught with SAS method. The research conducted in Tanduran Village Blora Regency in 2010, involved 40 research subjects comprising 20 subjects for experimental group with intensive bilingual method and 20 subjects with SAS method for controlling group. The data obtained were analyzed in two stages i.e. in the preliminary analysis and in hypothesis testing. The result of the research indicates, the reading and writing skills of literacy education participants in Samin community taught with intensive bilingual method are better than those taught wit SAS method.